Two-level factorial experiment for measurement of CD on equipment AA analyst - David M. Harutyunyan (Изд-во НАН РА)
The results of various methods in analytical chemistry are subject to different factors of countable number. Some of them may have insignificant, others significant impact on the results of analysis, which will orient the specialists to make true analysis to the extent of permissibility by holding their magnitudes at the optimal levels.
Keywords: Mathematics